2020
DOI: 10.1001/jamainternmed.2020.0111
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Lung Cancer Screening Program Websites

Abstract: recommends that individuals at high risk for lung cancer consider benefits and harms before pursuing lung cancer screening. Medical centers develop websites for their lung cancer screening programs, but to date little is known about the websites' portrayal of benefits and harms or what next steps they recommend for individuals considering screening.OBJECTIVE To assess the presentation of potential benefits and harms and recommended next steps on lung cancer screening program websites. DESIGN, SETTING, AND PART… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 23 publications
1
15
1
Order By: Relevance
“…Of the remaining 151 websites, (academic websites: n=76; community websites: n=75; Multimedia Appendix 1 ), 13 academic websites and 26 community websites had URL changes, largely because lung cancer screening information had been mapped to a different section of the website or a new website was built or refreshed (see an example in Multimedia Appendix 2 ). Therefore, of the 151 included websites, 39 website URLs were different from the original URLs reported by Clark and colleagues [ 14 ].…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…Of the remaining 151 websites, (academic websites: n=76; community websites: n=75; Multimedia Appendix 1 ), 13 academic websites and 26 community websites had URL changes, largely because lung cancer screening information had been mapped to a different section of the website or a new website was built or refreshed (see an example in Multimedia Appendix 2 ). Therefore, of the 151 included websites, 39 website URLs were different from the original URLs reported by Clark and colleagues [ 14 ].…”
Section: Resultsmentioning
confidence: 96%
“…The research team contacted the authors of a previously published article (Clark et al [ 14 ]) and obtained the list of 162 lung cancer screening program websites of academic centers (n=81) and state-matched community medical centers (n=81). Further detail on how the websites were selected is provided elsewhere [ 14 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of the SDM clinicians previously unknown to the patient might have been affiliated with LDCT screening centers, which may be biased toward LDCT. 3 …”
Section: Discussionmentioning
confidence: 99%
“…Some marketing strategies proven to be effective for LCS programs include hosting community screening days, direct consumer advertisements, educational websites and telephone access lines to facilitate self-referrals (22,23). Development of websites should be conscientious of presenting information that is balanced with regards to the benefits and harms of LCS, as a study evaluating LCS websites found that benefits were discussed twice as frequently as harms (24).…”
Section: Engaging Key Stakeholdersmentioning
confidence: 99%